STUDY ON ICHTHYOFAUNALDIVERSITY AND SPECIES RICHNESS INNAVEGAON RESERVOIR, DISTRICT GONDIA (M.S.), INDIA - Makade S.H; TelkhadeP.M; Bhogam H.A; Ramachandra P (The Bioscan, 2025)
Presenting data on the Navegaon Reservoir's Ichthyofaunal variety is the aim of the study. The reservoir is situated at 20°54'56.62"N latitude and 80°7'11.85"E longitude in the eastern part of Maharashtra State. Because of the numerous communities and forest area that encircle the reservoir, there is human incursion and cattle grazing. The 12-month study period began in November 2023 and ended in October 2024. There are several different kinds of fish at Navegaon Reservoir. In addition to providing baseline data on fish that can be utilized in subsequent research, this study provides information on the ichthyofaunal variation in this area. However, there is still more to be done, and new insights into Ichthyofaunal variety are emerging for the world to see. 23 species were investigates and identified by 8 families and 6 orders for the current investigation. Additionally, they recorded their IUCN Red and residential data status. Ichthyofaunal diversity in this study shows that species diversity rises during the post-monsoon season. The Cyprinidae family has eight species, while the Bagridae family has five. The Ambassidae family has four species, the Siluridae family has two, and the Clariidae, Notopteridae, Poecilidae, and Cichlidae families each have one. The Cyprinidae family dominates all of these families, as the current analysis shows. According to this study on ichthyofaunal variety, species diversity increases during the post-monsoon season, which is correlated with favorable conditions like a enough supply of food and water. Prior to the monsoon, the diversity was restricted, most likely as a result of the summertime water shortage.